(untitled) (Palíndromo, 2021)
suddenly three souls at a crossroads/ talking to debret about an old thing he wrote/ words ‘n’ thoughts/ objects ‘n’ whatnots/ not about sayin’ ‘n’ lyin’/ but rather tryin’ signifyin’/ there are dogs that bite/ they also chat and write/ mouth head/ cross uncross/ if the lion is dead/ who’s the boss/ pa pa la bas/ doubleness they are/ monkey jumpin’ in the daylight/ rhymin’ ‘n’ bluffin’ by the sky bright/ our ancestors once said/ calabashes and laughs/ as soon as they stopped the bled/ will soon become paths/ if you givin’ me crumbs/ I usin’ your hands to play me drums/ myself keep undyin’/ no motherfucker will stop me signifyin’